Teaching Quality and Students’ Self-Regulated Learning: The Challenges and Opportunities - Ijabah, Nur; Amrullah, Qadrina Lailyn (Journal of Linguistics and Social Studies, 2025)
Today’s education aims at creating lifelong learners. Therefore, education emphasizes creating independent students who can regulate their own learning. Through case study design, this present study was intended to seek in-depth information about teaching quality dimensions that promote self-regulated learning to the primary age students at one English learning community, Rita Home Library. The data was obtained through interviews and observation from both teachers and students. The data was analyzed by coding and theme analysis. The findings showed that setting challenging goal and task; engaging students in learning through metacognitive strategy; implementing clear rules and procedures; managing disciplinary and providing clear deadline; providing meaningful feedback; seeing mistake as a part of learning; being care and open to student’s need and emotion were found to be the predictors of teaching quality that were promoted by the teacher to the primary students at Rita Home Library.